TO DETERMINE ASSOCIATION BETWEEN LBW / IUGR / PRE-MATURITY IN NEONATES AND MATERNAL HEALTH IN A TERTIARY CARE HOSPITAL, KARACHI - Dr. Sidra Iqbal; Dr. Hifza Aiman; Dr. Ehsan Qadir; Dr. Kiran Minhas; Dr. Nimra Yousuf; Dr. Maryam Abid (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Low birth weight (LBW), intrauterine growth restriction (IUGR), and prematurity are major contributors to neonatal morbidity and mortality and are strongly influenced by maternal health.Objective: To determine the association between maternal health indicators and adverse neonatal outcomes (LBW, IUGR/SGA, prematurity) in a tertiary hospital in Karachi.Methods: Prospective observational study of consecutive mother–infant dyads using a standardized proforma. Maternal variables included hemoglobin, BMI, antenatal care (ANC) visits, booking status, and complications (PIH, DM/GDM). Neonatal outcomes included gestational age (GA), birth weight, and growth status (AGA/SGA/IUGR). Data were summarized as mean±SD or n (%). Exploratory associations were evaluated with crude odds ratios (OR) and 95% confidence intervals (CI) from 2×2 tables.Results: N = 26 dyads. Mean GA 32.84 ± 1.73 weeks; mean birth weight 1792.2 ± 500.3 g. Preterm (